The publics of public health in Africa. - Kelly, A; MacGregor, H; Montgomery, C (Taylor and Francis, 2016)
How do we understand the public character of public health in contemporary Africa? What are the parameters of community engagement in health care delivery, medical research and disease control programmes? To what extent is public health in Africa a project led by African Governments? Through what political processes and deliberative practices can African publics influence the priorities of research in health sciences and interventions which aim in broad terms to improve the health of such publics? Drawing insight from empirical research conducted with African scientists, nurses, community members, clinical trialists and policy-makers, this special section examines the multiple ways in which the public comes into being around public health provisioning and investigation in sub-Saharan Africa, its role and political reach. Collectively, these papers show how contestation and negotiation around different ideas about who the public is and what being public means can lead to the emergence of conflicting understandings, with implications for who and what is seen to represent the public interest, and for the acceptance of research and other interventions.